NON-CASH AGREEMENT IN PURCHASING BUILDING MATERIALS ACCORDING TO THE THEORY OF BAI' AL-DAIN - Azkia Rizkiana; Nahara Eriyanti; Abdullah (JURISTA: Jurnal Hukum dan Keadilan, 2025)
The present article aims to examine the legality of non-cash sales agreements. In the context of non-cash sales transactions, there exists a significant potential for harm to befall entrepreneurs in their capacity as sellers. This is primarily attributable to the potential for substantial price escalations. The present study adopts a qualitative, legal-empirical approach. The findings of this study indicate that the agreements reached by the parties regarding the purchase and sale of construction materials on a cash basis in Indra Jaya Pidie District include the recording of the identities of the parties involved, the details of the construction materials purchased, the agreed price of the construction materials, and the payment terms selected, such as 3 months, during which the buyer must settle the payment. However, it has been observed that certain purchasers have deviated from the terms of the agreement, a development that has the potential to occasion financial losses for Mulia Baru Store. Conversely, the new business store requires buyers to pay down to conduct cash transactions. Furthermore, buyers must consent to the imposition of a penalty in the event of non-compliance with the stipulated terms of payment.